Beautiful town : stories and essays - Satō, Haruo, 1892-1964 (Book collections on Project MUSE., 1996)
Six stories of amazing diversity and two critical essays revealing the understated Japanese ideals of beauty make up this volume, all translated into English for the first time. The title story is a utopian dream of a better city, populated by ideal people, that vanishes in a mirage. Another tale portrays the loneliness of a man unsuccessful with women. A third embellishes a bare Basho haiku about the man next door. Here too are the dream ballad of a Chinese prince, the imaginary world of a mad Japanese artist in Paris, and the probing search for an opium-drugged murderer. Sato's critical essays that conclude this volume have their themes in a exploration of the sad beauty of impermanence, the nature of enlightenment, the awareness of self, the merging of the instant and the eternal, and the "self-indulgent, unrestrained beauty" of the Japanese language